Fraud Awareness and Fraud Detection-Prevention Methods in The Indonesian Private and Public Sector - Iftikar Arif Yuri; Maya Rizki Sari (Global Financial Accounting Journal, 2022)
Purpose - To identify the level of awareness of fraud and methods for detecting and preventing fraud in several private and public companies in Indonesia. Research Method - This research uses a quantitative approach to examine these problems. In this study, the sample consisted of directors, managers/supervisors, accountants and employees including internal auditors from public and private sector organizations in several Indonesian companies, especially in Riau and West Sumatra Provinces. Data collection techniques used online-based using Google Form distributed to respondents. Findings - Total of 34 respondents who filled out the questionnaire resulted in the findings of around 76% of employees and managers working in private and public companies being aware of fraud and important factor for companies to consider. Meanwhile, in terms of tools/steps in preventing and detecting fraud in their organization, they are Internal Audit (94.1%), background check of prospective employees (91.2%) and also the Internal Control System (91.2%) which is a mechanism perceived effectiveness by employees within the organization. Implication - Gratification reports from workers, socialization of GCG understanding, if necessary cooperate with state financial transaction supervisors on suspicious transactions in the accounts of workers and workers' families. Moreover, providing understanding in the form of training and socialization about the dangers of fraud and fraud prevention efforts in their organization. Prevention and detection methods need to be developed in the organization.